Cytotoxicity evaluation of iron nitride nanoparticles for biomedical applications. Issue 10 (21st March 2021) - Shibata, Misaki; Kanetaka, Hiroyasu; Furuya, Maiko; Yokota, Kotone; Ogawa, Tomoyuki; Kawashita, Masakazu
Abstract: Magnetic nanoparticles are widely studied for their use in various therapeutic and diagnostic purposes. As biomaterials, their biocompatibility is as important as their magnetic properties. Iron nitride (Fex Ny ) has excellent magnetic properties, and thus Fex Ny nanoparticles could be useful as potential biomaterials. However, the biocompatibility of Fex Ny nanoparticles is yet to be investigated. In this study, we assessed the biocompatibility of Fex Ny nanoparticles by evaluating their direct‐contact cytotoxicity compared with that of magnetite nanoparticles (MNPs). Rat fibroblasts were incubated with the nanoparticle samples dispersed in culture medium at concentrations of 10, 50, and 100 μg/ml. The DNA concentration measurement, MTT assay, and trypan blue exclusion test were conducted after days 1 and 3 of incubation. After day 1, the cell viability decreased, and cell death increased with increasing sample concentration when compared with the control. However, after day 3, there were no significant differences when compared with the control, irrespective of the sample concentrations. Further, there were no significant differences between the Fex Ny nanoparticles and MNPs at the same concentrations in all the cytotoxicity evaluation tests. Therefore, it is suggested that Fex Ny nanoparticles might be as cytocompatible as the conventional MNPs.